Chinese Legal Reform: Achievements, Problems and Prospects - Ping, Jiang (Columbia Journal of Asian Law, 1995)
There is much to be achieved in Chinese legal reform m the next few years. According to the five year plan for legal reform drafted by the Eighth People’s Congress, close to 152 laws are expected to be enacted between 1993 and 1998. Although much of the work to develop these laws is on track, there are still many obstacles to be confronted on the way to attaining reform. In particular, there is the tension between the People’s Republic of China’s (“China”) old and new economic structures and between law and politics. Further, there is still a substantial gap to be bndged between the creation of legal norms and the enforcement of such norms. It is these three areas of difficulty that I will concentrate on in this article.